Additional letters function in the modern spoken Persian - إيفان كريم شناوه د. (lark, 2020)
Summary: Spoken language has its grammar, sometimes, it is completely different from written language. Unfortunately, grammar books authors don’t pay much attention to this very important aspect. Moreover, they refer to many important useful points, and sometimes they even refer to subjects unnoticed by others. Which make it imperative for people who desire to learn Persian to be aware of the grammatical structure of spoken Persian so they wouldn’t face any troubles when talking or pronouncing during everyday life. Hence, in this essay, we will address one of the most focal subjects which is, at the same time, considered of the most difficult in the spoken language and that is simple and complex additions and the function of each one of them. Keywords: Spoken Persian, Additional Letters, and Simple additional letters.